Non-adiabatic silica microfiber for strain and temperature sensors - Muhammad, M.Z.; Jasim, Ali Abdulhadi; Ahmad, Harith; Arof, Hamzah; Harun, Sulaiman Wadi (Elsevier, 2013)
A non-adiabatic silica microfiber is proposed for displacement or strain and high temperature sensing for the first time. The spectral response of the microfiber depends on the difference of the effective refractive indices of the core and the cladding modes, which induces resonant wavelength shift against the strain and temperature. It is observed that the peak wavelength of the transmitted comb spectrum is blue-shifted against displacement at a rate of 4.2 pm/µm. The temperature sensitivity of the device was measured to be 12.1 pm/℃ with an excellent linearity for temperature measurement up to 800 ℃.